2019
DOI: 10.1002/ctpp.201800152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ion mean free path length on plasma polarization behind a dust particle in an external electric field

Abstract: In this paper, a self‐consistent numerical model that describes the behavior of plasma around an isolated, highly charged dust particle is presented. Using the developed model, self‐consistent distributions of the space charge density and plasma potential in the presence of an external electric field are obtained. These distributions are thoroughly analysed though Legendre decomposition. For different dust plasma parameters, such as the radius of the dust particle, the amplitude of the external field, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…For complex plasmas, the main difficulties lie in estimating the multipole moments associated with the trapped ions. Recently, an iterative multipole expansion techniques has been applied for the particle potential in collisional complex plasmas that takes into account the trapped ion effect and slow ion flows [ 18 , 23 ]. It turns out that, in weak electric fields obeying , the long range multipole expansion of the potential converges fast and one can neglect the higher-order terms (see Figure 5 in Ref.…”
Section: Trapped Ions and Polarization Of The Ion Cloudmentioning
confidence: 99%
See 1 more Smart Citation
“…For complex plasmas, the main difficulties lie in estimating the multipole moments associated with the trapped ions. Recently, an iterative multipole expansion techniques has been applied for the particle potential in collisional complex plasmas that takes into account the trapped ion effect and slow ion flows [ 18 , 23 ]. It turns out that, in weak electric fields obeying , the long range multipole expansion of the potential converges fast and one can neglect the higher-order terms (see Figure 5 in Ref.…”
Section: Trapped Ions and Polarization Of The Ion Cloudmentioning
confidence: 99%
“…For estimations of a dipole moment associated with the trapped ions , we use the approximation that follows from expression (10) of Ref. [ 23 ], where we put and . Note that such is based on the self-consistent numerical model describing the polarization of a plasma around an isolated, highly charged particle in collisional limit and may be applicable in the case of low Mach numbers and (see Reference [ 23 ] for details).…”
Section: Trapped Ions and Polarization Of The Ion Cloudmentioning
confidence: 99%
“…In [17][18][19][20], the authors of this article demonstrated the results of calculations of a model in which the distributions of space charges and potentials were determined in a self-consistent manner also around spherical particles. This article presents the dependences of the density distribution and the space charge potential, as well as the dependence of the dipole moment of the "dust particle -ion cloud" system for nonspherical particles: a flattened and elongated ellipsoid.…”
Section: Introductionmentioning
confidence: 92%
“…Due to the fact that in the most detailed way the model has already been described in the works [17][18][19][20], only its main points will be described later. For convenience, a particle whose geometry is an elongated ellipsoid will be called ellipsoidal, and the geometry of which is a flattened ellipsoid -diskshaped.…”
Section: Modelmentioning
confidence: 99%
“…What will be the dependence of the charge of dust particles in the chain and the interparticle distance between them on the plasma parameters, and would such a chain will be stable? In references [38,39], a model was presented where the dependence of the spatial distributions of plasma around an isolated dust particle on various parameters of the particle itself, the surrounding plasma, and the external electric field was calculated. It was shown in reference [28] that the approximation of the dipole moment obtained in reference [38] can be used to describe with a good approximation the range of parameters in which dust particles self-organize into a chain.…”
Section: Introductionmentioning
confidence: 99%